Recalibrating the open method of coordination: towards diverse and more effective languages - Borrás, Susana; Radaelli, Claudio M. (Stockholm, 2010)
"The Open Method of Coordination is a relatively new form of cooperation within the European Union. It is used to adjust the policies of the member states in order to reach common goals. The method is controversial. Critics have argued that there are limited effects whereas supporters stress the achievements in terms of efficiency as well as the democratic credentials. This report analyses the merits and problems of the method, and presents specific proposals on how it can be developed, particularly in view of the Europe 2020 strategy."